2021
DOI: 10.3390/ijms22031445
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Response of Cervical Cancer Stem Cells Is Associated with Pretreatment Proportion of These Cells and Physical Status of HPV DNA

Abstract: Radio- and chemoresistance of cancer stem cells (CSCs) is considered as one of the possible causes of adverse results of chemoradiotherapy for various malignancies, including cervical cancer. However, little is known about quantitative changes in the CSC subpopulation in the course of treatment and mechanisms for individual response of CSCs to therapy. The purpose of the study was to evaluate the association of radiation response of cervical CSCs with clinical and morphological parameters of disease and featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a recent study by Zamulaeva et al (36), radioresistance of CC cells was found to be dependent on both integration of HPV DNA into the host cell genome and amount of this integration. This study demonstrated that the percentage of cancer stem cells (CSCs) increased after irradiation in tumors with fully integrated HPV DNA whereas the proportion of CSCs decreased in tumors with episomal or partly integrated forms.…”
Section: Hpv Physical State As a Prognostic Factor For Radiation Response In CCmentioning
confidence: 95%
“…In a recent study by Zamulaeva et al (36), radioresistance of CC cells was found to be dependent on both integration of HPV DNA into the host cell genome and amount of this integration. This study demonstrated that the percentage of cancer stem cells (CSCs) increased after irradiation in tumors with fully integrated HPV DNA whereas the proportion of CSCs decreased in tumors with episomal or partly integrated forms.…”
Section: Hpv Physical State As a Prognostic Factor For Radiation Response In CCmentioning
confidence: 95%
“…As for physiological EMT, that also accompanies SCC onset or progression occurs gradually, explaining why cells with intermediate phenotypes between the fully epithelial and the decidedly mesenchymal ones can be found in the squamous lesions of the uterine cervix [88][89][90][91][92][93][94][95][96][97]. Such a variety of phenotypes could depend on the multitude of EMT promoters that may be present in the cervix of HPV-infected women, and on the temporal sequence according to which cervical epithelial cells are exposed to these factors.…”
Section: The E5 E6 and E7 Proteins Of Hr-hpvs Trigger Emt In Cervical...mentioning
confidence: 99%
“…It has been proved that CD44 high CD24 low cervical cancer cells have the characteristics of CSCs. [34][35][36] CCSCs with CD44 high CD24 low were separated from CCCs (HeLa cells) by a magnetic separator. The proportion of CD44 high CD24 low cells in CCSCs was 97.2%, which was much higher than 1.52% in CCCs, indicating that the CD44 high CD24 low subpopulation has been successfully enriched from CCCS (Figure 2A).…”
Section: Isolation and Identification Of Ccscsmentioning
confidence: 99%